Penerapan Prinsip-Prinsip Edu-Agrowisata dalam Penataan Agrowisata Kuat Sihir sebagai Kawasan Edukasi - Erni Djuliawati; Nunik Hasriyanti; Achmad Eko Yanuar (Universitas Medan Area, 2026)
Agriculture is a vital sector in Indonesia’s economy, not only as a pillar of food security but also for its potential to be developed into educational tourism through the concept of edu-agrotourism. This concept integrates agricultur Agriculture is a vital sector in Indonesia’s economy, not only as a pillar of food security but also for its potential to be developed into educational tourism through the concept of edu-agrotourism. This concept integrates agricultural activities with recreation, education, and community empowerment, contributing to sustainable development. Kampung Gambut in Siantan Hilir, Pontianak, is an area rich in natural resources and agricultural diversity, yet its potential has not been optimally utilized due to limited infrastructure, weak management, and low environmental awareness. This study aiims to design the agro Wisata Kuat Sihir area as an educational tourism site with a focus on the edu-agrotourism concept. The planning process adopts a participatory and sustainable approach, using primary and secondary data collection, along with various analyses, including spatial analysis, tourism 3A (Attraction, Accessibility, and Amenities), and design emphasis. The results of this design are expected to offer long-term benefits to the local community through economic improvement, job opportunities, and increased understanding of sustainable agriculture, while also offering visitors a unique and educational tourism experience. al activities with recreation, education, and community empowerment, contributing to sustainable development. Kampung Gambut in Siantan Hilir, Pontianak, is an area rich in natural resources and agricultural diversity, yet its potential has not been optimally utilized due to limited infrastructure, weak management, and low environmental awareness. This study aiims to design the agro Wisata Kuat Sihir area as an educational tourism site with a focus on the edu-agrotourism concept. The planning process adopts a participatory and sustainable approach, using primary and secondary data collection, along with various analyses, including spatial analysis, tourism 3A (Attraction, Accessibility, and Amenities), and design emphasis. The results of this design are expected to offer long-term benefits to the local community through economic improvement, job opportunities, and increased understanding of sustainable agriculture, while also offering visitors a unique and educational tourism experience.